2007
DOI: 10.1002/smll.200600489
|View full text |Cite
|
Sign up to set email alerts
|

A Single‐Step Photolithographic Interface for Cell‐Free Gene Expression and Active Biochips

Abstract: We have developed a biochip platform technology suitable for controlled cell-free gene expression at the micrometer scale. A new hybrid molecule, "Daisy", was designed and synthesized to form in a single step a biocompatible lithographic interface on silicon dioxide. A protocol is described for the immobilization of linear DNA molecules thousands of base pairs long on Daisy-coated surfaces with submicrometer spatial resolution and up to high densities. On-chip protein synthesis can be obtained with a dynamic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
108
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(110 citation statements)
references
References 61 publications
0
108
0
2
Order By: Relevance
“…For brush assembly we used glass slides, 18 × 18 mm 2 , with nine separate reaction chambers enclosed in a sample holder (6)(7)(8). The density of DNA brushes on the same slide and duplicate slides could be fixed to within 5%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For brush assembly we used glass slides, 18 × 18 mm 2 , with nine separate reaction chambers enclosed in a sample holder (6)(7)(8). The density of DNA brushes on the same slide and duplicate slides could be fixed to within 5%.…”
Section: Methodsmentioning
confidence: 99%
“…We propose an in vitro methodology to emulate gene expression in a boundary-free compartment. The approach is based on a photolithographic biochip for fabricating dense phases of surface-bound DNA, thus forming DNA brushes (6)(7)(8). In general, brushes are formed when end-attached linear polymers collectively stretch because of excluded volume interaction when packed to distances at which there is significant overlap between neighboring molecules (9).…”
mentioning
confidence: 99%
“…[8][9][10][11] The biosynthetic reaction on surface of microchips was first realized by Buxboim et al and they developed and utilized the microchips assembled by photolithographic approach on silicon dioxide (SiO2) for controlling the cell-free expression. 7,8,12 This approach allows us to control the immobilized DNA and regulate the biosynthetic reactions in a more controlled manner. 7 Recently, it has been reported that there exists attenuation of protein synthesis in a translation coupled with a transcription system on DNA-grafted biochips, which is likely due to molecular crowding caused by the translational machinery.…”
Section: 5mentioning
confidence: 99%
“…Bar-Ziv and co-workers (Buxboim et al, 2007) recently developed an elegant approach to such a continuous system, which also provided the solution to another problem of current cell-free gene expression methods: in experiments conducted in bulk solution or microcompartments, reactions are not "localized." This is in contrast to the situation found in highly structured biological cells, where several stages of information-processing cascades are often co-localized.…”
Section: Cell-free Genetic Circuit Assemblymentioning
confidence: 99%
“…Different network connectivities resulted in distinct transitory expression domain patterns, resembling gap formation in the Drosophila embryo. Obviously, the above-mentioned chip-based expression system (Buxboim et al, 2007) should also be of great interest for the study of spatio-temporal effects and the realization of synthetic developmental systems in vitro.…”
Section: Artificial Developmentmentioning
confidence: 99%